Параметри спектрального та часового аналізу варіабельності серцевого ритму в умовах дисрегуляції апоптотичної активності при бронхо-легеневій патології у коморбідності із артеріальною гіпертензією - Тягла, Оксана Сергіївна; Тяглая, О. С.; Tyagla, O. S. (My University, 2019)
Згідно досліджень цілого ряду вчених, частота виникнення системної артеріальної гіпертензії у хронічних пульмонологічних хворих варіює від 0,4 до 27,7%. Мета: дослідження змін параметрів варіабельності серцевого ритму в залежності від рівня стану апоптотичних процесів у хворих із артеріальною гіпертензією на тлі хронічного обструктивного захворювання легень. Матеріали та методи. Було обстежено 25 чоловіків з діагнозом гіпертонічна хвороба ІІ стадії і хронічне обструктивне захворювання легень ІІ стадії без клінічно значущої супутньої патології, середній вік 51,72±1,22, більше 80% активні курці, індекс пачко-років 17,06±2,41, на шкідливий професійний фактор (виробничий) вказали 1/4 осіб. Результати. Index SDNN статистично достовірно (p<0,05) паралельно із елевацією значень маркера апопозу каспази-9 знижувався на 13,68%, порівнюючи між групами пацієнтів менше і більше IV квартиля згідно значень каспази-9. Значення LF у пацієнтів когорт менше і більше IV квартиля згідно значень каспази-9 демонструвало зниження на третину – 32,67% статистично достовірно (p<0,05). HF при наростанні активності процесів апоптозу згідно значень каспази-9 знизився найбільш суттєво – на 48,92% статистично достовірно (p<0,05). Висновок. У пацієнтів із хронічними обструктивним захворюванням легень на тлі артеріальної гіпертензії виявлена елевація стану симпатичного відділу вегетативної нервової системи і зниження активності парасимпатичної частини вегетативного забезпечення, що може потенційно асоціюватися із підвищеним ризиком появи серйозних кардіоваскулярних кейсів у пацієнтів із даною коморбідністю. Согласно исследованиям целого ряда ученых, частота возникновения системной артериальной гипертензии у хронических пульмонологических больных варьирует от 0,4 до 27,7%. Цель: исследование изменений параметров вариабельности сердечного ритма в зависимости от уровня состояния апоптотических процессов у больных с артериальной гипертензией на фоне хронического обструктивного заболевания легких. Материалы и методы. Было обследовано 25 мужчин с диагнозом гипертоническая болезнь II стадии и хроническое обструктивное заболевание легких II стадии без клинически значимой сопутствующей патологии, средний возраст 51,72±1,22, более 80% активные курильщики, индекс пачко-лет 17,06±2,41, на вредный профессиональный фактор (производственный) указали 1/4 человек. Результаты. Index SDNN статистически достоверно (p<0,05) параллельно с элевацией значений маркера апоптоза каспазы-9 снижался на 13,68%, сравнивая между группами пациентов меньше и более IV квартиля согласно значений каспазы-9. Значение LF у пациентов когорт меньше и более IV квартиля согласно значений каспазы-9 демонстрировало снижение на треть – 32,67% статистически достоверно (p<0,05). HF при нарастании активности процессов апоптоза согласно значений каспазы-9 снизился наиболее существенно – на 48,92% статистически достоверно (p<0,05). Вывод. У пациентов с хроническим обструктивным заболеванием легких на фоне артериальной гипертензии выявлена элевация состояния симпатического отдела вегетативной нервной системы и снижение активности парасимпатической части вегетативного обеспечения, которое может потенциально ассоци ироваться с повышенным риском появления серьезных кардиоваскулярных кейсов у пациентов с данной коморбидностью. According to numerous reports, the prevalence rate of systemic arterial hypertension in patients with chronic pulmonary diseases varies from 0.4 to 27.7%. The number of authors have shown a decrease in heart rate variability against the background of hypertension, mainly due to the SDNN (the standard deviation of the normal-to-normal RR intervals) and RMSSD (the root mean square of successive RRinterval differences), indicating a decrease in parasympathetic effects on the heart rhythm and a relative increase in sympathetic tone. Objective: to study changes in heart rate variability parameters depending on the level of apoptotic processes in patients with arterial hypertension against the background of chronic obstructive pulmonary disease. Materials and methods. We examined 25 men with a diagnosis of arterial hypertension stage II and chronic obstructive pulmonary disease stage II without clinically significant comorbidities, whose average age was 51.72±1.22; more than 80% of them were active smokers, pack-years index was 17.06±2.41, the harmful professional factor were indicated by 1/4 people. The verification of arterial hypertension was carried out in accordance with the Order of the Ministry of Health of Ukraine dated May 24, 2012 № 384. All patients were diagnosed with stage II of hypertension. Arterial hypertension degree was diagnosed in 12% patients – first, in 28% patients – second and in 60% patients, respectively, third. Participants expressed their willingness to be included in medical research. Results. Index SDNN statistically significantly (p<0.05) in parallel with the elevation of the values of the marker of apoposis of caspase-9 decreased by 13.68%, comparing between groups of patients less and more than IV quartile according to the values of caspase-9. The LF (Low Frequency power: frequency activity in the 0.04 - 0.15Hz range) value in patients with a cohort of less and more than IV quartile according to the values of caspase-9 showed a statistically significant decrease by 32.67% (p <0.05). HF (High Frequency power: frequency activity in the 0.15 - 0.40Hz range) with an increase in the activity of apoptosis processes according to the values of caspase-9 decreased most significantly significant, by 48.92% (p <0.05). To assess the direction, the tightness and the nature of the relationship between the indices between the studied variables, a regression analysis was conducted to construct a functional dependence. As independent argument (X) considered the level of caspase-9 activity, and as a dependent variable (Y) considered the indicator LF / HF (LF/HF Ratio: A ratio of Low Frequency to High Frequency). The obtained data indicated that the correlation between numerical variables in patients with caspase-9 level less than 4 quartiles had an unreliable character, while in patients with high expression of this cysteine protease the correlation obtained with a high degree of accuracy and adequacy was approximated by the model of exponential form, and namely: Y = 4,0578 * exp (0,0901 * X) at R = 0,547, R2 = 0,30, normalized R2 = 0,29, p = 0,0083). Conclusion. Elevation of the state of the sympathetic part of the autonomic nervous system and a decrease in the activity of the parasympathetic part of the autonomic support, which can potentially be associated with an increased risk of serious cardiovascular cases in patients with this comorbidity, were found in patients with chronic obstructive pulmonary disease against the background of arterial hypertension.
Параметры спектрального и временного анализа вариабельности сердечного ритма в условиях дисрегуляции апоптотической активности при бронхолегочной патологии в коморбидности с артериальной гипертензией
Parameters of spectral and temporal analysis of heart rate variability in the conditions of disregulation of apoptotic activity in bronchopulmonary pathology and comorbidity with arterial hypertension
Keywords: симпатовагальний баланс; каспаза-9; часовий і спектральний аналіз; коморбідність; апоптоз; симпатовагальний баланс; временной и спектральный анализ; коморбидность; sympathovagal balance; caspase-9; temporal and spectral analysis; comorbidity; apoptosis